2016
DOI: 10.1190/int-2015-0036.1
|View full text |Cite
|
Sign up to set email alerts
|

Prospecting for marine gas hydrate resources

Abstract: As gas hydrate energy assessment matures worldwide, emphasis has evolved away from confirmation of the mere presence of gas hydrate to the more complex issue of prospecting for those specific accumulations that are viable resource targets. Gas hydrate exploration now integrates the unique pressure and temperature preconditions for gas hydrate occurrence with those concepts and practices that are the basis for conventional oil and gas exploration. We have aimed to assimilate the lessons learned to date in globa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(51 citation statements)
references
References 49 publications
0
50
0
Order By: Relevance
“…Thus, the term BGHSZ is to be interpreted as base of structure I gas hydrate, or in line with previous suggested terminology, BS I GHSZ [e.g., Boswell et al, 2016;Paganoni et al, 2016]. We further want to emphasize that our study is not concerning the detailed and local gas hydrate concentrations with depth and any localized variations therein.…”
Section: 1002/2017gc006805mentioning
confidence: 99%
“…Thus, the term BGHSZ is to be interpreted as base of structure I gas hydrate, or in line with previous suggested terminology, BS I GHSZ [e.g., Boswell et al, 2016;Paganoni et al, 2016]. We further want to emphasize that our study is not concerning the detailed and local gas hydrate concentrations with depth and any localized variations therein.…”
Section: 1002/2017gc006805mentioning
confidence: 99%
“…Core analyses at those sites determined those reflections marked the top of highly concentrated gas hydrate zones [47,67]. Similar thin, positive amplitude reflections above the BSR have also been interpreted to represent the top of a concentrated gas hydrate zones along the Chilean margin [78].…”
Section: Bottom Simulating Reflections (Bsrs)mentioning
confidence: 90%
“…Incidences of blanking below the BSR could be from either gas saturated muds, or acoustic attenuation of the seismic wave as it passes through a thick GH zone. Drilling in the GoM demonstrated that blanking above the BSR reflects minor hydrate saturations and is not considered a prospective resource zone [47]. Thus, we do not include zones of blanking in our gas-in-place estimate.…”
Section: Seismic Evidence For Gas Source and Migration Pathways Into mentioning
confidence: 99%
See 1 more Smart Citation
“…To understand the spatial distribution of the reservoir quality in the upper unit, we performed an amplitude map analysis by using the reservoir top seismic horizon. Basically, NGH-bearing sediments generate an increase in impedance at the upper contact, which produces a positive or peak event (in the 0 • phase North American polarity) and a strong reflection in the seismic data (e.g., [15,17]). Therefore, seismic mapping of the amplitude is one of the generalized approaches to identify and evaluate the potential direct indication of NGH occurrence.…”
Section: Methods For the Understanding The Spatial Distribution Of Thementioning
confidence: 99%